Lighting and Ventilation-based Building Sun-Shading Design and Simulation Case in Cold Regions. (October 2018) - Sun, Nan; Cui, Yanqiu; Jiang, Yi; li, Shuting
Abstract: Building sun-shading design is an important aspect in new type energy-saving building technique. Based on the sun-shading and building integrated design case of a comprehensive teaching and laboratory building, we investigated the external shading and building integrated design practice in this paper. Indoor light and wind environment as well as energy-saving effects after setting external sun-shading device were analyzed by using simulation software. The results illustrated that the indoor thermal environment and comfort level could be highly improved through reasonable design of external sun-shading while the energy consumption of air conditioners was also reduced. This research offered direct reference for the building sun-shading project and promoted the sun-shading and building integration design.